2016
DOI: 10.18632/oncotarget.7749
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous p53 and ASPP2 expression enhances rAdV-TK/GCV-induced death in hepatocellular carcinoma cells lacking functional p53

Abstract: Suicide gene therapy using herpes simplex virus-1 thymidine kinase (HSV-TK) in combination with ganciclovir (GCV) has emerged as a potential new method for treating cancer. We hypothesize that the efficacy of HSV-TK/GCV therapy is at least partially dependent on p53 status in hepatocellular carcinoma (HCC) patients. Using recombinant adenoviral vectors (rAdV), TK, p53, and ASPP2 were overexpressed individually and in combination in Hep3B (p53 null) and HepG2 (p53 wild-type) cell lines and in primary HCC tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…It was observed in breast cancer cells that the HSV-TK/GCV system induced p53-dependent DNA damage responses and cell cycle arrest, perturbing mitochondrial homeostasis through membrane potential dysfunction and release of cytochrome c into the cytoplasm in neuroblastoma cells [ 519 , 525 , 526 ]. Similar findings were reported in hepatocellular carcinoma cells using an adenovirus method of delivery for HSV-TK [ 527 ]. The HSV-TK/GCV system has also been seen to be effective in tumor models in mice [ 528 , 529 , 530 , 531 ].…”
Section: Viral Kinasessupporting
confidence: 87%
“…It was observed in breast cancer cells that the HSV-TK/GCV system induced p53-dependent DNA damage responses and cell cycle arrest, perturbing mitochondrial homeostasis through membrane potential dysfunction and release of cytochrome c into the cytoplasm in neuroblastoma cells [ 519 , 525 , 526 ]. Similar findings were reported in hepatocellular carcinoma cells using an adenovirus method of delivery for HSV-TK [ 527 ]. The HSV-TK/GCV system has also been seen to be effective in tumor models in mice [ 528 , 529 , 530 , 531 ].…”
Section: Viral Kinasessupporting
confidence: 87%
“…The main obstacle is that these cancer stem cells are often in a state of dormancy which impairs the treatment effects of chemotherapeutic drugs (9). Some recent studies have shown that the herpes simplex virus thymidine kinase (HSVtk) gene and the complementary treatment with ganciclovir (GCV) exert marked antitumor effects against HCC by promoting apoptosis and inhibiting angiogenesis (10,11). However, it is still difficult to prevent the recurrence of liver tumors (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Liu et al. further confirmed that exogenous p53 plays an important role in improving cell death in hepatocellular carcinomas (HCC), therefore enhancing therapeutic effects in HCC patients who lack normal p53 functions [32].…”
Section: Discussionmentioning
confidence: 95%
“…Honda and his colleagues reported that the transcriptional effects of exogenous p53 gene could be promoted by an upstream estrogen response, leading to lower transfection rates by inhibiting the cell cycle [31]. A study by Liu et al further confirmed that exogenous p53 plays an important role in improving cell death in hepatocellular carcinomas (HCC), therefore enhancing therapeutic effects in HCC patients who lack normal p53 functions [32].…”
Section: Discussionmentioning
confidence: 99%